The Impact Of Using Social Sites On Academic Performance For Students At Jordanian Universities - Manal A. Altawalbeh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
this research sought to determine the applications preferred by students and investigated the effect of using social sites on academic performance by ungraduated students in Jordanian universities. 400 questionnaires were distributed to undergraduate students in Jordanian universities. The results showed a statistically significant relationship between use of social network sites and performance of academic. Facebook, WhatsApp, youtube were the favored social network sites choices among students while LinkedIn and Instagram were the least reported choices. Also, the excessive use of social sites without real supervision from teachers or careful planning of employing its applications may affect the academic performance of Jordanian university students. Additionally, students must be guided and learn to properly manage their time when spending social network sites for purposes of education. The results of this research may be employed to mention effective ways to integrate social network sites into learning activities without affecting student performance.